Environmental impact of infant feeding type, accessories used and maternal dietary habits: The GREEN MOTHER-I project, a cross-sectional study protocol - Rosa Maria Cabedo-Ferreiro; Liudmila Liutsko; Judit Cos-Busquets; Rosa García-Sierra; Margalida Colldeforns-Vidal; Azahara Reyes-Lacalle; Mª Mercedes Vicente-Hernández; Miriam Gómez-Masvidal; Laura Montero-Pons; Gemma Cazorla-Ortiz; Pere Torán-Monserrat; Concepció Violán; et al. (Nutrition Journal, 2024)
Abstract Introduction Breastfeeding (BF) is the healthiest form of nutrition for babies and is recommended exclusively (EBF) for at least the first six months of life. The carbon footprint of formula feeding (FF) has been studied, but that of BF is unknown. Aim To identify the environmental impact of three types of infant feeding taking into account the accessories needed and the diet of postpartum women in the baby’s first month of life. Methods This is a multicentre, cross-sectional study conducted in the Barcelona North Metropolitan Area (Catalonia, Spain). The participating sites are primary care settings that will recruit 408 postpartum women (4–6 weeks) as per inclusion/exclusion criteria. The data will be collected through a GREEN MOTHER Survey that includes 4 dimensions: 1) socio-demographic and clinical data; 2) data on the newborn and accessories used in infant feeding; 3) general data on the mother's diet (food consumption habits), and 4) recording of 24 h of the mother’s diet. The data analysis will be performed to check the prevalence of infant feeding types at birth and month 1, as well as a comparative analysis of three types of infant feeding on environmental impact (climate change; water consumption, and scarcity). Ethics. This project was approved by the Research Ethics Committee of the Jordi Gol i Gurina University Institute Foundation for Primary Health Care Research (IDIAP) under code 22/101-P dated 22/02/2023. Discussion A second phase of the GREEN MOTHER study is planned, which will consist of an educational intervention to promote breastfeeding, nutrition and sustainability. This intervention will be based on the results obtained in Phase I. We expect that the project results – through the publication and dissemination of scientific papers and reports among relevant stakeholders (association of community midwives, healthcare and primary care attention professionals and the public) – will increase public awareness of breastfeeding and its impact on sustainability. Trial registration Both phases of the GREEN MOTHER study protocol were registered in ClinicalTrials.gov, NCT05729581.